Kyrgyz Republic : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kyrgyz Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Poverty Reduction and Growth Facility (PRGF) arrangement approved in February 2005 has aimed to preserve solid growth while maintaining low inflation, further reduce poverty, and tackling the Kyrgyz Republic's large external debt overhang. The March 2005 'Tulip Revolution' has provided an opportunity to advance reforms, particularly in the area of governance, but lingering political tensions slowed progress. The political turmoil adversely has affected growth, but inflation remained low until recently. The political difficulties also slowed efforts to improve the business environment, although some progress has been made.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet